Interplay between Iron Homeostasis and the Osmotic Stress Response in the Halophilic Bacterium Chromohalobacter salexigens - Argandoña, Montserrat (American Society for Microbiology (ASM), 2010)
In this study, the connection between iron homeostasis and the osmostress response in the halophile Chromohalobacter salexigens was investigated. A decrease in the requirement for both iron and histidine and a lower level of siderophore synthesis were observed at high salinity, and these findings were correlated with a lower protein content in salt-stressed cells. A six-gene operon (cfuABC-fur-hisI-orf6 operon) located downstream of the ectABC ectoine synthesis genes was characterized. A fur strain (in which the ferric iron uptake regulator Fur was affected) had the Mn resistance phenotype typical of fur mutants, was deregulated for siderophore production, and displayed delayed growth under iron limitation conditions, indicating that fur encodes a functional iron regulator. hisI was essential for histidine synthesis, which in turn was necessary for siderophore production. Fur boxes were found in the promoters of the cfuABC-fur-hisI-orf6 and ectABC operons, suggesting that Fur directly interacts with DNA in these regions. Fur mediated the osmoregulated inhibition of cfuABC-fur-hisI-orf6 operon expression by iron and functioned as a positive regulator of the ectABC genes under high-salinity conditions, linking the salt stress response with iron homeostasis. Excess iron led to a higher cytoplasmic hydroxyectoine content, suggesting that hydroxyectoine protects against the oxidative stress caused by iron better than ectoine. This study provides the first evidence of involvement of the iron homeostasis regulator Fur as part of the complex circuit that controls the response to osmotic stress in halophilic bacteria.